Tax and spending shocks in the open economy: Are the deficits twins? - Mathias Klein; Ludger Linnemann (Sveriges Riksbank, 2019)
We present evidence on the open economy consequences of US fiscal policy shocks identified through proxy-instrumental variables. Tax shocks and government spending shocks that raise the government budget deficit lead to persistent current account deficits. In particular, the negative response of the current account to exogenous tax reductions through a surge in the demand for imports is among the strongest and most precisely estimated effects. Moreover, we find that the reduction of the current account is amplified when the tax reduction is due to lower personal income taxes and when the government increases its consumption expenditures. Historically, a much larger share of current account dynamics has been due to tax shocks than to government spending shocks.
Keywords: E32; E62; F41; 330; Tax policy; government spending; proxy-vector autoregressions; current account; twin deficits